2015
DOI: 10.1117/1.oe.55.1.011004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonation on the linear and nonlinear dynamic properties of cement-based materials

Abstract: Abstract. Carbonation causes a physicochemical alteration of cement-based materials, leading to a decrease of porosity and an increase of material hardness and strength. However, carbonation will decrease the pH of the internal pore water solution, which may depassivate the internal reinforcing steel, giving rise to structural durability concerns. Therefore, the proper selection of materials informed by parameters sensitive to the carbonation process is crucial to ensure the durability of concrete structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…During the progress of concrete carbonation, the existing pores and microcracks are deposited by the carbonation product CaCO 3 . The molar volume of carbonated products is higher than that of hydrates, resulting in a decrease in the porosity of concrete and an increase in the density of concrete [3,4]. Then the fundamental amplitude A 1 increases while the harmonic amplitude A 2 decreases as ultrasonic attenuation decreases.…”
Section: Non-linear Parameters Change Of Carbonated Concrete With Two...mentioning
confidence: 99%
See 1 more Smart Citation
“…During the progress of concrete carbonation, the existing pores and microcracks are deposited by the carbonation product CaCO 3 . The molar volume of carbonated products is higher than that of hydrates, resulting in a decrease in the porosity of concrete and an increase in the density of concrete [3,4]. Then the fundamental amplitude A 1 increases while the harmonic amplitude A 2 decreases as ultrasonic attenuation decreases.…”
Section: Non-linear Parameters Change Of Carbonated Concrete With Two...mentioning
confidence: 99%
“…The spectrum was verified to detect carbonation reaction early. During concrete carbonation, the pores and microcracks in concrete change as a result of the carbonation products [3,4], and these changes significantly impact the material non-linearity. The feasibility of the non-linear Resonant Ultrasound Spectroscopy (NRUS) technique was verified by Bouchaala et al [5] in concrete carbonation by measuring the resonant frequency shift of the signal in a given mode with the resonant peak amplitude [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Bouchaala et al [4], reported that resonant ultrasonic nonlinear parameters have the feasibility of measuring concrete carbonation. Eiras et al [5] used resonance ultrasonic spectroscopy technology to study the effect of concrete carbonation on the linear and nonlinear dynamic properties of cement-based materials. The linear and nonlinear dynamic properties can be used to deem material against carbonation in laboratory tests, whereas concrete has inherent nonlinearity due to its material composition.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the need for new physical parameters that provide further information on the mechanical performance of concrete upon DEF has been claimed in several study reviews [9][10][11]. In recent years, the evaluation of the nonlinear mechanical behavior through resonant experiments has been satisfactorily applied to assess different durability distresses in concrete, such as alkali-silica reaction [12][13][14] freezing-thawing damage [15][16][17], thermal damage [18,19], and carbonation [20,21]. The evaluation of the nonlinear properties of concrete upon the development of DEF has seldom been studied.…”
Section: Introductionmentioning
confidence: 99%